Evaluation of Physicochemical and Microbiological Parameters of Drinking Water Supplied from Distribution Systems of Kathmandu Municipality - Shakya, Prabin; Joshi, Tista P; Joshi, Dev R; Bhatta, Dwij R (Nepal Journal of Science and Technology, 2013)
Microbial pathogens in drinking water are primary cause in gastrointestinal and waterborne diarrheal diseases. Public health authorities still have not achieved success in controlling the most common waterborne diseases in Nepal. The objective of this study was to assess the quality of drinking water supplied from distribution system of Kathmandu. A total of 114 water samples were collected from 4 distribution stations. The physicochemical and microbiological analyses of water were conducted. Heterotrophic plate count (HPC), detection of enteric pathogenic bacteria and antibiotics susceptibility test were done. Distinct variations in physicochemical parameters were observed. The mean free residual chlorine was found 0.24mg/l. Total Coliforms were found in 61.4% (70/114) of water samples among which 15.7% (11/70) had thermotolerant Coliforms. In distance, coliforms were found higher in far points (p=0.002). All thermotolerant Coliforms were identified as Escherichia coli. Mean HPC of water was found log103.15. The mean HPC of water (p=0.003) was found higher in far point. In collected samples, 10 different enteric bacteria were isolated in which E. coli was found most predominant followed by Pseudomonas spp., Citrobacter spp., Klebsiella spp., Shigella spp., Proteus spp., Enterobacter spp. Non-Typhii Salmonella spp., Providencia spp., Edwardsiella spp. In antibiotics susceptibility test, Gentamicin and Ofloxacin were found most efficient (100%) and whereas Ampicillin (11.5%) was least effective. Multiple antibiotics resistance was found among 5.3% of isolates. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 179-184 DOI: http://dx.doi.org/10.3126/njst.v13i2.7733